Consistent population activity on the scale of minutes in the mouse hippocampus. Issue 5 (28th February 2022) - Liu, Yue; Levy, Samuel; Mau, William; Geva, Nitzan; Rubin, Alon; Ziv, Yaniv; Hasselmo, Michael; Howard, Marc
Abstract: Neurons in the hippocampus fire in consistent sequence over the timescale of seconds during the delay period of some memory experiments. For longer timescales, the firing of hippocampal neurons also changes slowly over minutes within experimental sessions. It was thought that these slow dynamics are caused by stochastic drift or a continuous change in the representation of the episode, rather than consistent sequences unfolding over minutes. This paper studies the consistency of contextual drift in three chronic calcium imaging recordings from the hippocampus CA1 region in mice. Computational measures of consistency show reliable sequences within experimental trials at the scale of seconds as one would expect from time cells or place cells during the trial, as well as across experimental trials on the scale of minutes within a recording session. Consistent sequences in the hippocampus are observed over a wide range of time scales, from seconds to minutes. The hippocampal activity could reflect a scale‐invariant spatiotemporal context as suggested by theories of memory from cognitive psychology.